2010
DOI: 10.1128/aac.01263-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunomodulatory and Organism-Associated Molecules on the Permeability of anIn VitroBlood-Brain Barrier Model to Amphotericin B and Fluconazole

Abstract: Amphotericin B (AMB) is used to treat fungal infections of the central nervous system (CNS). However, AMB shows poor penetration into the CNS and little is known about the factors affecting its permeation through the blood-brain barrier (BBB). Therefore, we studied immunomodulatory and organism-associated molecules affecting the permeability of an in vitro BBB model to AMB. We examined the effects of interleukin-1 beta (IL-1␤), tumor necrosis factor alpha (TNF-␣), lipopolysaccharide (LPS), lipoteichoic acid (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Similar CSF and brain data for AmBd, L-AMB, and ABLC (i.e., CSF and tissue/plasma concentration ratios of Ͻ0.3) have been recorded for rabbits (92). In contrast to the case with posaconazole, inflammation does not seem to increase the concentration of any amphotericin formulation in the brain, at least in animals (40,92). To overcome these potential limitations, intraventricular instillation of AmBd via an Ommya reservoir has been used for severe cerebral infections (93,94,95).…”
Section: Brain and Cerebrospinal Fluidsupporting
confidence: 48%
See 1 more Smart Citation
“…Similar CSF and brain data for AmBd, L-AMB, and ABLC (i.e., CSF and tissue/plasma concentration ratios of Ͻ0.3) have been recorded for rabbits (92). In contrast to the case with posaconazole, inflammation does not seem to increase the concentration of any amphotericin formulation in the brain, at least in animals (40,92). To overcome these potential limitations, intraventricular instillation of AmBd via an Ommya reservoir has been used for severe cerebral infections (93,94,95).…”
Section: Brain and Cerebrospinal Fluidsupporting
confidence: 48%
“…(ii) physiological factors, such as inflammation, which may increase tissue permeability, i.e., by disruption of normal physiological barriers such as the blood-brain barrier (29,40); the underlying disease (41), which may result in a range of effects, including modification of plasma protein composition and hence drug binding (42,43,44); the recruitment of drug-containing phagocytic cells, i.e., the "dump truck phenomenon," which may increase drug concentrations at the site of infection (12,13,32,45,46); drug export via pumps, e.g., for itraconazole and P-glycopro- Fluid multiples are from g/ml concentrations. *, autopsy data; in these cases, the multiples are based on plasma C max values at the same dose in volunteers (188).…”
Section: Determinants Of Distribution Of Antifungal Agents Into Tissuesmentioning
confidence: 99%
“…These in vivo findings correlate well with data from the in vitro BBB model, which showed a significantly increased permeation of DAMB and LAMB in the infected model (10). Several mechanisms to account for permeability changes are possible, including the induction of local cytokine responses in infected tissue, the mechanical disruption created by hyphal and pseudohyphal invasion, and local enzymatic disruption of the BBB from Candida proteases and phospholipases (21).…”
Section: Discussionsupporting
confidence: 84%
“…However, since amphotericin B shows limited penetration into CSF, little is known about the factors affecting its efficacy in CNS tissue or its permeation through the BBB in HCME. Our earlier work demonstrated that the proinflammatory cytokines induced by organism-associated molecules significantly increase the permeability of the BBB, as demonstrated by a decreased mean TEER in an in vitro BBB model (10). Consistent with the known properties of dexamethasone and other corticosteroids, dexamethasone increased the mean TEER and decreased the permeability of the BBB to amphotericin B.…”
Section: Discussionsupporting
confidence: 71%
“…In the present case, itraconazole was the only available antifungal drug and was initially used for treatment. However, itraconazole penetrates the blood brain barrier poorly and this was therefore substituted with fluconazole, which achieves much higher concentration in the CNS parenchyma (Arndt and others 1988, Kethireddy and Andes 2007, Pyrgos and others 2010). Treatment with fluconazole has been reported to be effective in resolving neurological signs in dogs, although prolonged treatment courses are required (Tiches and others 1998, O'Toole and others 2003, Lavely and Lipsitz 2005) and the prognosis remains guarded (Malik and others 2006).…”
Section: Figurementioning
confidence: 99%